1958
DOI: 10.1121/1.1909527
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Influence of Flow on Sound Attenuation in Absorbing Ducts

Abstract: The influence of a turbulent air stream on the sound attenuation in ducts, lined with sound absorbing materials or structures of different kinds, has been experimentally investigated. For linings consisting either of porous materials or sufficiently damped Helmholtz resonators, decrease of absorption with increasing flow velocity has been observed, together with an increase of the frequency of maximum absorption in the case of the resonators. Somewhat surprising results have been obtained for undamped or weakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1961
1961
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…Such an instability, when coupled with a resonant acoustic mode within the system, can give rise to pure tones as investigated by Meyer, Mechel, and Kurtze, 16 Dean, 17 Adams, 18 Tsui and Flandro, 19 and Bauer and Chapkis. 20 Details of the instability across a single perforation ͑hole͒ were simulated in the experimental study of Ronneberger.…”
Section: A Previous Related Investigationsmentioning
confidence: 96%
“…Such an instability, when coupled with a resonant acoustic mode within the system, can give rise to pure tones as investigated by Meyer, Mechel, and Kurtze, 16 Dean, 17 Adams, 18 Tsui and Flandro, 19 and Bauer and Chapkis. 20 Details of the instability across a single perforation ͑hole͒ were simulated in the experimental study of Ronneberger.…”
Section: A Previous Related Investigationsmentioning
confidence: 96%
“…In In order to investigate the conditicns for sound amplification the absorbers were varied., It is an important experience from the experiments that all dimensians have to be kept constant over the entire length of the duct with utitost care and accuracy, Small deviati-ns in the dt•ensions of the resonators cause frequency deviations and changes of the wave impedance-which influence and often prevent sound amplification, It is learnt from the results reported in [2] that the sound amplification is critically dependent on the shape of the flow-side end of the resonator necks, Resonators were built the values of the acoustical elements cf which -vibrating mass and resilient volume -were identical with the Helmholtz resonators described above. The necks, however, were given a shape so that a stronger interference with the f]•hw was to be expected (see Fig•r8)…”
mentioning
confidence: 99%
“…However, for specific liners and under particular flow conditions, some experiments have shown that a convective hydrodynamic instability may grow on the liner and is likely to lead to sound amplification [1,2,3,4,5,6]. Evidence of such instabilities have been shown as well numerically [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the main density ρ 0 and the speed of sound a 0 are taken as constants 1 . The Mach number of the main flow is denoted M 0 , the maximum and mean Mach numbers of mean velocity profile are denoted respectively M andM .…”
Section: Linearised Equationsmentioning
confidence: 99%